Changing Rates of Self-Harm and Mental Disorders by Sex in Youths Presenting to Ontario Emergency Departments: Repeated Cross-Sectional Study. (November 2019) - Gardner, William; Pajer, Kathleen; Cloutier, Paula; Zemek, Roger; Currie, Lisa; Hatcher, Simon; Colman, Ian; Bell, Dayna; Gray, Clare; Cappelli, Mario; Duque, Daniel Rodriguez; Lima, Isac
Objective: To document the rates of intentional self-harm and mental disorders among youths aged 13 to 17 years visiting Ontario emergency departments (EDs) from 2003-2017. Methods: This was a repeated cross-sectional observational design. Outcomes were rates of adolescents with (1) at least 1 self-harm ED visit and (2) a visit with a mental disorder code. Results: Rates of youths with self-harm visits fell 32% from 2.6/1000 in 2003 to 1.8 in 2009 but rose 135% to 4.2 by 2017. The slope of the trend in self-harm visits changed from –0.18 youths/1000/year (confidence interval [CI], –0.24 to –0.13) during 2003 to 2009 to 0.31 youths/1000/year (CI, 0.27 to 0.35) during 2009 to 2017 ( P < 0.001). Rates of youths with mental health visits rose from 11.7/1000 in 2003 to 13.5 in 2009 (15%) and to 24.1 (78%) by 2017. The slope of mental health visits changed from 0.22 youths/1000/year (CI, 0.02 to 0.42) during 2003 to 2009 to 1.84 youths/1000/year (CI, 1.38 to 2.30) in 2009 to 2017 ( P < 0.001). Females were more likely to have self-harm ( P < 0.001) and mental health visits ( P < 0.001). Rates of increase after 2009 were greater for females for both self-harm ( P < 0.001) and mental health ( P < 0.001). Conclusions: Rates of adolescents with self-harm and mental health ED visits have increased since 2009, with greater increases among females. Research is required on the determinants of adolescents' self-harm and mental health ED visits and how they can be addressed in that setting. Sufficient treatment resources must be supplied to address increased demands for services.